Microbially Induced Calcium Carbonate Plugging for Enhanced Oil Recovery - Chenpeng Song; Derek Elsworth (Geofluids)
Plugging high-permeability zones within oil reservoirs is a straightforward approach to enhance oil recovery by diverting waterflooding fluids through the lower-permeability oil-saturated zones and thereby increase hydrocarbon displacement by improvements in sweep efficiency. Sporosarcina pasteurii (ATCC 11859) is a nitrogen-circulating bacterium capable of precipitating calcium carbonate given a calcium ion source and urea. This microbially induced carbonate precipitation (MICP) is able to infill the pore spaces of the porous medium and thus can act as a potential microbial plugging agent for enhancing sweep efficiency. The following explores the microscopic characteristics of MICP-plugging and its effectiveness in permeability reduction. We fabricate artificial rock cores composed of Ottawa sand with three separate grain-size fractions which represent large (40/60 mesh sand), intermediate (60/80 mesh sand), and small (80/120 mesh sand) pore sizes. The results indicate a significant reduction in permeability after only short periods of MICP treatment. Specifically, after eight cycles of microbial treatment (about four days), the permeability for the artificial cores representing large, intermediate, and small pore size maximally drop to 47%, 32%, and 16% of individual initial permeabilities. X-ray diffraction (XRD) indicates that most of the generated calcium carbonate crystals occur as vaterite with only a small amount of calcite. Imaging by SEM indicates that the pore wall is coated by a calcium carbonate film with crystals of vaterite and calcite scattered on the pore wall and acting to effectively plug the pore space. The distribution pattern and morphology of microbially mediated CaCO3 indicate that MICP has a higher efficiency in plugging pores compared with extracellular polymeric substances (EPSs) which are currently the primary microbial plugging agent used to enhance sweep efficiency.